Application of Newton's and Chebyshev's Methods to Parallel Factorization of Polynomials (Journal of Computational Mathematics, 2001)
In this paper it is shown in two different ways that one of the family of parallel iterations to determine all real quadratic factors of polynomials presented in [12] is Newton's method applied to the special equation (1.7) below. Furthermore, we apply Chebyshev's method to (1.7) and obtain a new parallel iteration for factorization of polynomials. Finally, some properties of the parallel iterations are discussed.
Keywords: Newton's method; Chebyshev's method; Parallel iteration; Factorization of polynomial.